The Effect of Rabeprazole on LES Tone in Experimental Rat Model. (1st August 2013) - Duman, Mustafa; Polat, Erdal; Ozer, Mahmut; Demirci, Yeliz; Yasar, Necdet Fatih; Akyuz, Cebrail; Uzun, Orhan; Peker, Kıvanc Derya; Genc, Ece; Yol, Sinan
ABSTRACT: Introduction: Despite adequate treatment with proton pump inhibitors (PPIs), symptoms of gastroesophageal reflux disease (GERD) may remain persistent as well as Barrett's esophagus may emerge. It may be proposed that the relaxant effect of PPIs on the smooth muscles may lead to resistance of symptoms. The aim of this study is to investigate effects of rabeprazole on the lower esophageal sphincter (LES) pressure with a rat model. Materials and Methods: Sixteen rats were grouped as control and treatment groups. After obtaining LES tissues followed by a 60 min equilibration period for stabilization, contractile response to carbachol was obtained by application of single dose of carbachol to have a final concentration of 10 −6 M in the organ bath. After the contractions reached a plateau, concentration-response relationships for rabeprazole were obtained in a cumulative manner in the treatment group. Results: In the carbachol contracted LES preparations; 1.5 × 10 −6 and 1.5×10 −5 M of rabeprazole caused 6.08% and 11.34% relaxations respectively which were not statistically significant. However, mean integral relaxation value for 4.5 × 10 −5 M of rabeprazole was 17.34% and this relaxation was significant compared with controls. Conclusions: In the present study, rabeprazole caused no direct significant change in LES tone in the therapeutic dose range applied to the organ bath. However, rabeprazole at the high dose caused a significant decrease in the LES tone.